Prevalence of epithelial abnormalities and high‐risk human papilloma virus in cervicovaginal Pap smears of population subgroups as a guide toward evidence‐based best practice. Issue 7 (23rd February 2019) - Siddiqi, Anwer; Webb, Fern; Smotherman, Carmen; Shuja, Sania; Mubeen, Aysha; Lai, Kent
Abstract : Background: The 2012 American Society for Colposcopy and Cervical Pathology Consensus Guidelines provide information for managing abnormal cervical cancer screening tests and cancer precursors. According to these guidelines for Pap smear diagnosis of Atypical squamous cells of undetermined significance, reflex high risk (HR) human papilloma virus (HPV) genotyping is required among women 21 years of age or older. Whereas, in women of 30 to 65 years of age, HR‐HPV can be ordered by the clinicians as part of co‐testing with any diagnosis and every 5 years with a negative Cervico‐Vaginal Pap test (CVPT). Methods: A retrospective review of the CoPath database of the Pathology Department at the University of Florida, College of Medicine Jacksonville, FL, was performed to identify North Florida (NF) women who underwent CVPT and HR‐HPV testing between 2006 and 2014. The women were stratified by race and age, respectively. Results: The study included 19, 933 CVPTs. Significant differences in the outcomes' distributions were found among age and race groups, respectively. Highest prevalence of HPV positivity was found in African American women, and in 14‐ to 20‐year‐old women, respectively. Twenty‐ to 30‐year‐old women had the highest percentage (59%) of epithelial abnormality. The most common HR‐HPV genotypic distribution was other HR‐HPV. Conclusions: This study underscores the importance of using both HR‐HPV and CVPT for screening for cervical cancer, and confirms the need for special focus on managing high‐risk populations subgroups, such as African American women, and women of ages 14 to 20 years especially in high‐risk populations.